EFEKTIVITAS LEG EXERCISE DAN KOMBINASI DEEP BREATHING TERHADAP MEAN ARTERIAL PRESSURE (MAP) PADA PASIEN POST OPERASI - Vita Dwi Futmasari; Rodhi Hartono; Mardiyono Mardiyono (JENDELA NURSING JOURNAL, 2019)
Background : Patient post-operative had experienced a critical period after surgery and anesthesia, the body's physiological interference occurred among hypotension. The impact was hypoperfusion for the infarction brain tissue and death. Therefore, it was necessary interventions trigger cardiovascular system used the Leg Exercises and Deep Breathing exercises.Objectives : To examine the effectiveness combination of Leg Exercises and Deep Breathing for mean arterial pressure.Methods : This study used Quasi Experiment randomized pre-test post-test control group design, These samples were 51 respondents in Roemani Semarang Hospital on  January 2nd to February 24th 2019. The technique collected at lottery simple random sampling and the tests used Kruskal Wallis post hoc Mann Whitney.Results : The results showed the highest average to increase MAP for the difference pre-post and the post was the combination group with p=0,000 on Kruskal Wallis test. The post hoc Mann Whitney test showed average to increase MAP in the control group and the Leg Exercise is same with the p value0,05 and the combination higher than Leg Exercise with the p value0,05. It’s meant that the combination most effectively to increase MAP and had clinical significant with p=0,000.Conclusion : This study presented the combination of Leg Exercise and Deep Breathing most effectively to prevent hypotension in patients post-surgery with spinal anesthesia in Roemani Semarang Hospital.